2020
DOI: 10.1186/s12870-020-02395-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular adaptation to salinity fluctuation in tropical intertidal environments of a mangrove tree Sonneratia alba

Abstract: Background: Mangroves have adapted to intertidal zones-the interface between terrestrial and marine ecosystems. Various studies have shown adaptive evolution in mangroves at physiological, ecological, and genomic levels. However, these studies paid little attention to gene regulation of salt adaptation by transcriptome profiles. Results: We sequenced the transcriptomes of Sonneratia alba under low (fresh water), medium (half the seawater salinity), and high salt (seawater salinity) conditions and investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 81 publications
1
32
0
2
Order By: Relevance
“…Located at the transition between ocean and land, mangrove sediments experienced the tidal uctuation day after day [63]. Probably due to the continuous scouring of sur cial sediments by tides and the deposition of salinity in depth [64,65], a continuous increase of salinity with depth of mangrove sediments was observed in our study. More interestingly, in agreement with the paddy soil [66] and salt marsh [67], salinity was identi ed as the most important environmental lter for shaping the diazotrophic community structure in mangrove sediments, as revealed by our RDA and SEM results.…”
Section: Discussionsupporting
confidence: 59%
“…Located at the transition between ocean and land, mangrove sediments experienced the tidal uctuation day after day [63]. Probably due to the continuous scouring of sur cial sediments by tides and the deposition of salinity in depth [64,65], a continuous increase of salinity with depth of mangrove sediments was observed in our study. More interestingly, in agreement with the paddy soil [66] and salt marsh [67], salinity was identi ed as the most important environmental lter for shaping the diazotrophic community structure in mangrove sediments, as revealed by our RDA and SEM results.…”
Section: Discussionsupporting
confidence: 59%
“…Other factors such as exposure to flooding due to tidal inundation and high salinity are among the potential factors in the low progression rate or possible death of the juveniles. Many studies reported that even the juveniles of salt-tolerant species A. marina and S. alba cannot withstand high salinity and are having low growth performances in this condition (Ball et al 1995;Kodikara et al 2018;Cheng et al 2020;Feng et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In general, salt adaptation is both a long-term and dynamic process and involves many morphological, physiological, cellular, and molecular processes (Feng et al, 2020;Ma et al, 2013;Munns and Tester, 2008;Seki et al, 2002). Mangrove trees can induce specific salt-responsive genes and transcription factors to facilitate adaptation to intertidal environments (Feng et al, 2020). The salt overly sensitive (SOS) pathway is a well-defined signaling pathway for controlling ion homeostasis at the cellular and tissue level (Ji et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Vivipary and high salt tolerance are particularly common in mangroves and rare in other woody plants. Salt tolerance is a long-term and dynamic process influenced by multiple genes involving many morphological, physiological, molecular, and cellular processes (Feng et al, 2020;Ma et al, 2013;Munns and Tester, 2008;Seki et al, 2002). Several important signaling pathways have been identified, especially the salt overly sensitive (SOS) signaling pathway, as well as Ca 2+ -dependent and ABA signaling pathways (Ji et al, 2013).…”
Section: Introductionmentioning
confidence: 99%